Clinical and Scintigraphic Findings in Radiation Myositis Complicating the Intraperitoneal Administration of 198Au - Němec, J.; Kubalt, J.; Vohnout, S.; Schubert, J.; Sudek, J.; Šebek, V. (Nuklearmedizin - NuclearMedicine, 1965)
Praeperitoneal administration of colloidal 198Au complicating the treatment of anascitic ovarian cancer is reported. Typical scintiscans and various clinical findings of muscle necrosis and radiation myositis are described. Administration of larger amount of saline solution preceding the radiogold instillation controlled by simultaneous scintiscanning are suggested as safety measures in patients when no ascitic fluid is present.Les auteurs s’occupent des complications observées à la suite des injections prae-péritonéales de 198Au colloïdal dans le traitement du cancer ovarien sans ascite. Ils décrivent des scintigraphies typiques, des différentes observations cliniques de nécrose musculaire et de myosite actinique. En cas d’absence d’ascite il est recommandé, comme mesure de sécurité, d’administer une quantité assez grande de solution de chlorure de sodium avant l’injection de l’or radioactif en contrôlant par scintigraphic la répartition de la substance.Es wird berichtet über Komplikationen bei präperitonealer Injektion von kolloidalem Radiogold zur Behandlung des Ovarialkarzinoms ohne Aszites. Typische Scintiscans, verschiedene klinische Befunde der Muskelnekrose und Strahlenmyositis werden beschrieben. Als Sicherheitsmaßnahme bei Patienten ohne Aszites wird empfohlen, vor dem Radiogold eine größere Menge Kochsalzlösung zu injizieren bei gleichzeitiger Kontrolle durch Scintiscan.